Status & Development of Institutional Repositories In Malaysia (Public & GLC Universities) - Salleh Hudin, Mustaffa (Perpustakaan Tuanku Syed Faizuddin Putra (PTSFP), Universiti Malaysia Perlis, 2018)
Organized by Tuanku Syed Faizuddin Putra (PTSFP) Library, Universiti Malaysia Perlis, 12th-13th April 2018 at Hotel Seri Malaysia Kangar, Perlis.